RETRACTED: New integrated system for raising poultry as a factor of increasing its productivity and metabolic status - Semenenko Marina; Kuzminova Elena; Osepchuk Denis; Semenenko Ksenia; Svistunov Andrey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001